Impact of Environmental Thermal Stimulation on Activation of Hypothalamic Neuronal Nitric Oxide Synthase during the Prenatal Ontogenesis in Muscovy Ducks - Valery Dunai; Barbara Tzschentke (The Scientific World Journal)
The aim of the study is to investigate the influence of prenatal temperature stimulation on neuronal NO synthase (nNOS) expression in the anterior hypothalamus of Muscovy duck embryos. Experiments were performed on embryonic day (E) E20, E23, E28, and E33 using histochemistry for identification of the nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) as marker of NOS-containing neurons. Until the experiments, all duck embryos were incubated under standard temperature conditions (37.5∘C). During 3 hours before the start of the experiments, one group was incubated at 37.5∘C (control group), the second was warm-experienced at 39∘C, and the third was cold-experienced at 34∘C. In normal and warm-incubated duck embryos, nNOS activity could be first detected on E23. Particularly, after cold stimulation, a significant increase in nNOS activity was found in all embryos investigated even on day 20. Warm stimulation obviously induces the opposite effect, but at later embryonic age (E33). It can be concluded that probably in late-term bird embryos NO acts as a mediator of the neuronal cold pathway in the anterior hypothalamus, which might be improved by prenatal cold stimulation.